Anti-inflammatory action of components from Melastoma malabathricum - Md Pisar, Mazura; Darnis, Deny Susanti; Mat Ali, Rasadah (Informa Healthcare, 2007)
Ethnic folklore or empirical therapeutic uses of plant parts have often provided the early indication of the possibility of discovering some pharmacologically active substance from a plant. Melastoma malabathricum L. (Melastomaceae), locally known as sendudok putih, is a small shrub. Traditional medicinal uses include diarrhea, dysentery, ulcers, wound care, and piles. In the search for natural compounds useful against anti-inflammatory activity, a-amyrin, betulinic acid, and isolated flavonoids, including quercetin and quercitrin, were assessed in vitro by determining their inhibitory effects on platelet activating factor (PAF) binding to rabbit platelets using 3H-PAF as a ligand. The results indicated that quercetin, quercitrin, a-amyrin, and betulinic acid showed inhibition of PAF receptor binding with IC50 values of 33.0, 45.4, 20.0, and 22.2 mM, respectively. The IC50 values of these compounds were comparable to Cedrol (13.1 mM), which is a known PAF receptor antagonist. These results suggest that natural flavonoid and pentacyclic triterpenes from M. malabathricum possess selective antagonistic activity toward PAF and could be an attractive candidate as a natural anti-inflammatory compound.